The FN quadratic marking/dropping probability function - M. Kadhum, Mohammed; Hassan, Suhaidi (IEEE Computer Society, 2009)
The gateway queuing performance depends on the marking/dropping probability function chosen. This function plays an important role in managing the gateway buffer. It maps the current congestion level to marking/dropping probability that is applied to each arriving packet. Active queue management mechanisms drop arriving packets probabilistically before the gateway buffer gets full. Fast Congestion Notification (FN) mechanism is a proactive queue management mechanism that marks/drops packets before a buffer overflow happens to avoid congestion. FN avoids the queue overflows by controlling the instantaneous queue size below the optimal queue size, and control congestion by keeping the average arrival rate close to the outgoing link capacity.Upon arrival of each packet, FN uses the instantaneous queue size and the average arrival rate to calculate the packet marking/dropping probability. This paper presents the derivation of the FN quadratic marking/dropping probability function based on the assumption that the average packet arrival rate changes during the control time constant period with the constant acceleration.